Awareness and knowledge of vape among students of Universiti Teknologi Mara (UiTM) Selangor Kampus Puncak Alam - Mohammad Sabri, Syuhadah Hanim (2016)
Vapes are battery-powered devices designed to deliver nicotine and other substances, including flavouring, to the user in the form of a vapour. They mimic the sensations of traditional cigarettes but do not burn or create tobacco smoke or ashes. Nor do they contain tar, the main cause of cancer in smokers. In Malaysia, the study on the level of awareness and knowledge about vape is very limited. Therefore, this study is done to evaluate the level of awareness and knowledge about vape in Malaysia, specifically among the students of UiTM Selangor, Kampus Puncak Alam. The assumption is that the students of UiTM have high awareness and knowledge about vape as there are many articles and media statements about vape in the country. This study was aimed to identify the prevalence of awareness about vape among UiTM Puncak Alam students, to evaluate the level of knowledge about vape among the students of UiTM Puncak Alam and to identify the perception towards vape among the students. This is a cross-sectional study because it covers a selected sample of population. An adapted questionnaire was distributed to 3 77 students from different faculties in U iTM Puncak Alam. The students were asked to fill in the questionnaire by themselves. It was a self-administered written questionnaire in English. The prevalence of awareness of vape among the students is high (100%) and this high prevalence come from younger age of students, students from health related faculty as well as business-related faculty. Most of the students have moderate level of knowledge of vape and most of them also have bad perception towards vape where they perceived that vape is harmful to the health of the users and vape should be banned in public area. In conclusion, the students of UiTM Puncak Alam have high awareness towards vape but moderate level of knowledge of vape. They also have bad perception towards vape which corresponds to their level of knowledge of vape.